Psychometric Characteristics, Cross-Cultural Adaptation and Validation of the Slovenian Version of the Victorian Institute of Sports Assessments for Gluteal Tendinopathy Questionnaire (VISA-G) - ROŠKAR Samo; ROJC Marina; PODOVŠOVNIK Eva; TREBŠE Rihard (Sciendo, 2023)
Greater trochanteric pain syndrome (GTPS) denotes several disorders around the lateral aspect of the hip. GTPS may develop in native hips as well as after total hip arthroplasty (THA). It is estimated that 5−12% of patients suffer from GTPS after primary THA. Despite the prevalence of GTPS, it is hard to diagnose and manage it properly. The VISA-G questionnaire was developed as a patient-reported outcome measurement tool for evaluation of GTPS. The aims of the present study were to evaluate the reliability of the VISA-G Slovenian and its construct and criterion validity.